Business Cycles in the Eastern Caribbean Economies : The Role of Fiscal Policy and Interest Rates - Carneiro, Francisco (World Bank, Washington, DC, 2016)
This paper analyzes the business cycle characteristics of the economies of the Organization of Eastern Caribbean States using a model of a small open economy subject to interest rate and fiscal expenditure shocks and financial frictions. The paper shows that macroeconomic aggregates in this region are quite volatile, with consumption exhibiting higher volatility than gross domestic product. The analysis also finds that in these economies real interest rates are highly volatile and strongly countercyclical with gross domestic product and other macroeconomic aggregates. Similarly, fiscal expenditures show significant volatility, but are pro-cyclical with gross domestic product. The results suggest two major directions for designing policies to help reduce the volatility experienced by the Organization of Eastern Caribbean States economies. First, Organization of Eastern Caribbean States countries should seek a greater openness to international financial markets, which could help them smooth out the effects of fundamental shocks, such as shocks to technology and terms of trade, and shocks associated with natural hazards. However, this removal of international financial barriers needs to be accompanied by improvements in domestic financial conditions, as this would reduce the vulnerability of these economies to country risk premium shocks. Second, the Organization of Eastern Caribbean States region should try harder to move toward a countercyclical fiscal policy stance, as this could help to stabilize the domestic risk premium and cushion the negative effects of interest rate shocks on economic activity, hence reducing volatility.